The Surprisingly Swift Decline of US Manufacturing Employment - Pierce, Justin R.; Schott, Peter K. (American Economic Review, 2016)
This paper links the sharp drop in US manufacturing employment after 2000 to a change in US trade policy that eliminated potential tariff increases on Chinese imports. Industries more exposed to the change experience greater employment loss, increased imports from China, and higher entry by US importers and foreign-owned Chinese exporters. At the plant level, shifts toward less labor-intensive production and exposure to the policy via input-output linkages also contribute to the decline in employment. Results are robust to other potential explanations of employment loss, and there is no similar reaction in the European Union, where policy did not change. (JEL D72, E24, F13, F16, L24, L60, P33)